Use Of The Yamaha F100B Outboard Engine As a Populsion On The Rinca and Bawean Survey Boats: Penggunaan Mesin Tempel Yamaha F100B Sebagai Penggerak Pada Kapal Survey Boat Rinca Dan Bawean - Aldiantofas, Rizky Dwi; Akbar, Ali (Universitas Muhammadiyah Sidoarjo, 2024)
The aim of this research is to determine the use of the Yamaha F100B outboard engine as a propulsion for the Rinca and Bawean survey boats. The research was carried out within one month, namely August to September 2023. This research was carried out using practical field work methods. The variables in this research were the specification,work process, fuel efficiency system, superiority, and environmental impact. The method in this research uses the observation method, namely the method of collecting data by recording directly while in the field. The research results show that the use of a Yamaha F100B outboard motor as a propulsion is able to provide adequate thrust for the survey vessel, with efficient fuel consumption. In the context of survey vessels, the reliability and speed of these motors are important factors in supporting successful marine survey operations.